2016
DOI: 10.1155/2016/2545168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moderate Aerobic Exercise on Cognitive Abilities and Redox State Biomarkers in Older Adults

Abstract: We used a moderate aerobic exercise program for 24 weeks to measure the positive impact of physical activity on oxidative stress and inflammatory markers and its association with cognitive performance in healthy older adults. A total of 100 healthy subjects (65–95 Yrs) were randomly classified into two groups: control group (n = 50) and exercise group (n = 50). Cognitive functioning, physical activity score, MDA, 8-OHdG, TAC, and hs-CRP were assessed using LOTCA battery, prevalidated PA questionnaire, and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 83 publications
3
35
0
5
Order By: Relevance
“…Westernised FPs (abundant in meat, sweets, fried foods, and refined grains) correlated with biomarkers of inflammation and atherogenesis [260]. Apart from food and in contrast to the abovementioned "antioxidants," moderate aerobic exercises positively affect both redox state biomarkers and cognitive abilities in older adults [261]. To consider another complicated problem, peripheral neuropathy is among the prevailing neurologic conditions encountered by physicians and toxicologists [192,262].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Westernised FPs (abundant in meat, sweets, fried foods, and refined grains) correlated with biomarkers of inflammation and atherogenesis [260]. Apart from food and in contrast to the abovementioned "antioxidants," moderate aerobic exercises positively affect both redox state biomarkers and cognitive abilities in older adults [261]. To consider another complicated problem, peripheral neuropathy is among the prevailing neurologic conditions encountered by physicians and toxicologists [192,262].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…It was consistent with other clinical interventions' findings. It was revealed that moderate aerobic training for 24 weeks has a positive significant effect in improving cognitive functions by modulating the redox and inflammatory status of older adults (65-95 years); in this study they used MDA, 8-hydroxy-2-deoxyguanosine and total antioxidant capacity as biomarkers of oxidative stress [1]. Similarly, Beltran Valls et al found that 12 weeks of low-frequency, moderate-intensity training reduced serum levels of myeloperoxidase, a marker of oxidative stress, in old community-dwelling people (70-75 years) [2].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, direct measurement of the levels of oxidative products has been carried out in some studies. Alghadir et al showed that, in a population of elderly undergoing a 24-week program of PA, there was a significant decrease in oxidative stress markers, including high sensitivity C-reactive protein (hsCRP), malondialdehyde (MDA), and 8-hydroxyguanine (8-OHdG) when compared to subjects who did not exercise [19]. Similarly, a 12-week program of Nordic walking in elderly women showed a decrease in levels of MDA oxidation products (p = 0.01) [20].…”
Section: Effect Of Pa On Inflammatory Markers and Oxidative Stress Mementioning
confidence: 99%